Answer:
![A.\ \ \left( f+g\right) \left( x\right) =-2x^(2)-2x+8](https://img.qammunity.org/2023/formulas/mathematics/high-school/ijmqbtrkr8p8irbziaxe6nf3zvbatftbs7.png)
Explanation:
We are Given :
• f(x) = 3x + 5
• g(x) = -2x² - 5x + 3
Recall that : (f + g)(x) = f(x) + g(x)
Then
(f + g)(x) = 3x + 5 + -2x² - 5x + 3
= -2x² + (3x - 5x) + (5 + 3) (Just put like terms together)
= -2x² + (-2x) + (8) (Simplify)
= -2x² - 2x + 8 (Get rid of the parentheses)
Conclusion :
![\left( f+g\right) \left( x\right) =-2x^(2)-2x+8](https://img.qammunity.org/2023/formulas/mathematics/high-school/b8khzu3leaxyb31y8leyy4ppsi1yle6d03.png)